Perlindungan Hukum Bagi Para Pihak Dalam Perjanjian Kredit Dengan Jaminan Hak Taggungan - Hayuning Widiasari (Res Judicata, 2018)
First, Execution security rights as a consequence of credit guarantees for legal protection for the benefit of creditors. This thesis raised about how the principles of justice that exist in the security rights can provide equal justice between the parties that the creditor and the debtor.As part of the creditors get credit guarantee from the debtor, the debtor has an attachment relationship with the lender if a default then the lender can do to guarantee the execution of the credit. The debtor in accordance with tracts of credit that has been approved by both parties in this case is the creditor and the debtor could not resist the execution unless resolve all obligations that have been agreed by both parties.Execution of dependents sometimes be biased in its implementation because the debtor not be included in the determination of the auction price execution. Prices are sometimes determined not correspond to the actual sale price, but only in accordance with debt that is owned. It needs legal protection fairest to protect the debtor in order to apply the principles of justice can be essential